Adsorption of Zn and Cd Ions on Vermiculite in Buffered and Unbuffered Aqueous Solutions - Xiaofu Wu; Hailan Zhou; Fang Zhao; Chong Zhao (Adsorption Science & Technology)
Studies of Zn 2+ and Cd 2+ ion adsorption onto vermiculite from buffered and unbuffered aqueous solutions were conducted in order to compare their ion adsorption behaviours in different systems. The use of buffer reagents had a strong and negative effect on the adsorption of the metal ions under study. The experimental data obtained from both the buffered and unbuffered solutions could not be described by a single traditional adsorption isotherm due to the effect of the adsorbent concentration (W). The equilibrium ion concentration in bulk solution (Z) and the equilibrium ion adsorption density (X/W ratio) decreased with increasing W in both buffered and unbuffered systems, indicating that the use of a buffer solution is not an effective measure for eliminating the effect of the adsorbent concentration. The addition of competitive ions (H + , Cd 2+ and Zn 2+ ) greatly reduced the adsorption of the target metal ion. Within the pH range tested (initial pH < 7), the competitive effect of H + ions was equivalent to that of Zn 2+ and Cd 2+ ions. In unitary, binary and ternary systems, highly significant linear correlations were obtained between the change in the ionic strength (ΔI) and the quantity of ion adsorption. The results obtained suggest that it is not necessary to control the ionic strength in ion adsorption experiments because ΔI is a function of ion adsorption, and the use of buffer reagents has a negative effect on ion adsorption.